Pemeriksaan Asam Urat Kolesterol dan Gula Darah pada Masyarakat Pengunjung yang Berada di Kawasan Monumen Nasional Jakarta - Fajar, In Rahmi Fatria; Fitri, Dewi Rahma; Hidayat, Febri; Komarudin, Dede (Lembaga Publikasi Ilmiah Nusantara, 2025)
Improving public health is a key priority in health development in Indonesia. Health education and health check-ups are interrelated activities and play a crucial role in both promotive and preventive efforts. Health education aims to increase public knowledge, awareness, and healthy living behaviors, while health check-ups serve as early disease detection and risk factor identification. This study aims to improve health in an integrated manner by increasing knowledge and early disease detection among the public in the Jakarta area, especially those visiting the National Monument. The methods used were experimental and lecture methods. Data were collected through pre-test and post-test questionnaires on counseling participants and the results of mass health check-ups. The examination results showed that the majority of visitors suffered from gout and hypertension. Health education for visitors went smoothly. In conclusion, this community service activity went smoothly and was well received by the community.